2018
DOI: 10.1155/2018/9869343
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Anemia in Geriatric Population Visiting Outpatient Department at the University of Gondar Referral Hospital, Northwest Ethiopia: Implication for Community-Based Screening

Abstract: Objective This study is aimed at assessing the magnitude and its associated factors of anemia in geriatric population visiting outpatient department at the University of Gondar referral hospital, northwest Ethiopia. Method A cross-sectional study was conducted among elder patients in Gondar town, North Gondar District, in May 2013. A total of 200 randomly selected geriatric population participated in the study. Summary statistics were computed and presented in tables and figure. Both bivariate and multivariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 43 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Normocytic anemia was the most common type in our study, seen in more than half of cases, similar to previous studies. [1516]…”
Section: Discussionmentioning
confidence: 99%
“…Normocytic anemia was the most common type in our study, seen in more than half of cases, similar to previous studies. [1516]…”
Section: Discussionmentioning
confidence: 99%
“…A hospital-based study done in Tanzania revealed that more than two-third of the participants were having either moderate or severe anaemia (27). However, there were contrasting results in other studies where mild anaemia was mainly identified in the older adult population (2,5). Studies done in the community and elder homes revealed mild anaemia as the commonest type of anaemia (28)(29)(30)(31)(32).…”
Section: Research Lettermentioning
confidence: 97%
“…Anaemia in older adults, being one of the commonest medical problems in clinical practice, often goes unnoticed unless it is severe or causes deterioration of the underlying medical condition (1). Older adults have many age-related physiological changes which make the clinical presentation of anaemia atypical and unnoticeable (2). The onset of anaemia is often insidious and patients tend to adapt to the clinical deterioration (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anemia is a multifactorial condition and a common public health problem in older adults, particularly in developing countries with a high prevalence in Africa and Southeast Asia. According to the WHO criteria, a hemoglobin value <12g/dL in women and <13 g/dL in men is defined as anemia in the elderly ( 3 ). Blood hemoglobin concentration decreases with aging; thus, the prevalence and incidence of anemia increase with aging ( 4 ).…”
Section: Introductionmentioning
confidence: 99%